1987
DOI: 10.1193/1.1585419
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Friction Damped Braced Steel Frames under Simulated Earthquake Loads

Abstract: This paper presents the results obtained from tests of a new friction damping system, which has been proposed in order to improve the response of steel Moment Resisting Frames (MRF) and Braced Moment Resisting Frames (BMRF) during severe earthquakes. The system consists of a mechanism containing brake lining pads introduced at the intersection of frame cross-braces. Seismic tests of a three storey Friction Damped Braced Frame (FDBF) model were performed on an earthquake simulator table. The experimental result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 1 publication
0
60
0
3
Order By: Relevance
“…To offset the losses due to creep, it is customary to increase the design slip load by 3% to 5% for the actual friction damper [14]. Furthermore, past research [15] has shown that a change in the slip load up to 20% of the optimum value does not have a significant effect on the building response. This was also evident in the 20-story building study where a 20% change in the optimum slip load (20 kips) would not have a noticeable effect on the peak interstory drift.…”
Section: Creep Effects and Relaxation Of Boltsmentioning
confidence: 99%
“…To offset the losses due to creep, it is customary to increase the design slip load by 3% to 5% for the actual friction damper [14]. Furthermore, past research [15] has shown that a change in the slip load up to 20% of the optimum value does not have a significant effect on the building response. This was also evident in the 20-story building study where a 20% change in the optimum slip load (20 kips) would not have a noticeable effect on the peak interstory drift.…”
Section: Creep Effects and Relaxation Of Boltsmentioning
confidence: 99%
“…It is possible to improve the energy absorption capacity through the use of the friction damping mechanism of a Pall EDOR. Filiatrault and Cherry [7] analysed the hysteretic behaviour of friction-damped braced frames with Pall EDORs. But in the case of the Filiatrault and Cherry analysis, there was a hypothesis that seemed unconvincing.…”
Section: Characteristics Of Pall Frictional Edorsmentioning
confidence: 99%
“…The most notable feature of the Pall frictional EDOR is the frictional damping mechanism [7]. If the diagonal braces of an ordinary braced frame structure were designed not to buckle in compression, a simple friction joint could be inserted in each diagonal.…”
Section: Characteristics Of Pall Frictional Edorsmentioning
confidence: 99%
See 1 more Smart Citation
“…-Reported experiments (Tyler 1985, Filiatrault and Cherry 1987, Fitzgerald et al 1989, Anagnostides and Hargreaves 1990, Aiken and Kelly 1990, Richter et al 1990, Whittaker et al 1991, Grigorian et al 1993, Yang and Popov 1995, Wu and Ou 2003, Morgen and Kurama 2004, Ng and Xu 2006, Vial et al 2005, Ricles et al 2006, Zhu et al 2006, Tsai et al 2008, Morgen and Kurama 2008, Iyama et al 2009) do not yield enough information about those questions, as they are mostly oriented to check the global validity of particular devices or assemblies. -The numerical simulation constitutes a challenging issue as the dynamic behavior of friction devices is highly nonlinear, as discussed previously.…”
Section: Fig 2 Hysteresis Loops Of Energy Dissipatorsmentioning
confidence: 99%